Effect of phenylbutazone administration on the enteroinsular axis in horses with insulin dysregulation - Kate L. Kemp; Jazmine E. Skinner; François‐René Bertin (Journal of Veterinary Internal Medicine)
Abstract Background Phenylbutazone is prescribed for laminitis‐associated pain and decreases glucose and insulin responses to an oral glucose test (OGT) in horses with insulin dysregulation (ID). Hypothesis/Objectives Investigate the effect of phenylbutazone administration on the enteroinsular axis in horses. Animals Sixteen horses, including 7 with ID. Methods Randomized cross‐over study design, with horses assigned to treatment with phenylbutazone (4.4 mg/kg IV q24h) or placebo (5 mL 0.9% saline). On Day 9 of treatment, an OGT was conducted, followed by a 10‐day washout period, administration of the alternative treatment, and repetition of the OGT. Glucose‐dependent insulinotropic polypeptide (GIP), and active glucagon‐like peptide 1 and 2 (aGLP‐1 and GLP‐2) concentrations were determined by ELISA. The effects of ID status and treatment on peptide concentrations were assessed using t tests and analyses of variance. Results Horses with ID had significantly higher maximum GIP concentrations (Cmax) than controls (median, 279.1; interquartile range [IQR], 117.5‐319.4 pg/mL vs median, 90.12; IQR, 74.62‐116.5 pg/mL; P = .01), but no significant effect of ID was detected on aGLP‐1 and GLP‐2 concentrations. In horses with ID, phenylbutazone treatment significantly decreased GIP Cmax compared with placebo (168.1 ± 59.26 pg/mL vs 242.8 ± 121.8 pg/mL; P = .04), but no significant effect of phenylbutazone was detected on aGLP‐1 and GLP‐2 concentrations. Conclusion and Clinical Importance Glucose‐dependent insulinotropic polypeptide, aGLP‐1 and GLP‐2 do not mediate the decrease in glucose and insulin concentrations observed after phenylbutazone administration. Only GIP was repeatedly associated with ID status, calling into question the role of the enteroinsular axis in ID.